Dimensi Politik dari Misi Pembebasan Gereja bagi Orang Miskin dan Pemeliharaan Alam Ciptaan - Jebadu, Alexander (P3TK, Sanata Dharma University, 2017)
Churchs ministry is to stand in solidarity with the poor, oppressed and to safeguard creation. This call requires the Church which means all Christians to get involved in the worlds socio-political affairs. Consequently, the Church is and must be political in a broad and noble sense. A prophetic liberative mission of the Church includes promoting love, justice, solidarity and fraternity among the entire human family, defending the dignity of the human person in its fullness and safeguarding the integrity of creation in cooperation with all people of good will. The Church will be in position of supporting the just worlds socio-economic and political affairs, but will denounce unjust practices in any form that do not respect the dignity of the human person, destroying livelihoods of the poor or do not safeguard creation as common heritage of humankind. This is to be done without violating the principle of justice and of separation between religion and state.